2000
DOI: 10.1097/00006534-200003000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Staged Breast Reconstruction with Saline-Filled Implants in the Irradiated Breast: Recent Trends and Therapeutic Implications

Abstract: A retrospective review was performed of one surgeon's experience with 40 consecutive patients who had undergone two-stage saline-filled implant breast reconstruction and radiation during the period from 1990 through 1997. A randomly selected group of 40 other two-stage saline-filled implant breast reconstructions from the same surgeon and time period served as controls. This review was undertaken because of the absence of specific information on the outcome of staged saline implant reconstructions in the radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
155
2
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(171 citation statements)
references
References 26 publications
7
155
2
7
Order By: Relevance
“…Our results demonstrated that the CC rate was similar in the IBR and DBR groups (15.3 and 11.9%, P = 0.616), as was the esthetic outcome, which is known to be highly dependent on the CC rate [47]. Furthermore, the capsular formation rate compared favorably with the rates reported in series of immediate breast reconstructions plus adjuvant RT [37,[46][47][48]. The CC rate varies considerably in the literature-from 17 to 68%-because of the inhomogeneity of the selected patients and the surgical procedures used.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our results demonstrated that the CC rate was similar in the IBR and DBR groups (15.3 and 11.9%, P = 0.616), as was the esthetic outcome, which is known to be highly dependent on the CC rate [47]. Furthermore, the capsular formation rate compared favorably with the rates reported in series of immediate breast reconstructions plus adjuvant RT [37,[46][47][48]. The CC rate varies considerably in the literature-from 17 to 68%-because of the inhomogeneity of the selected patients and the surgical procedures used.…”
Section: Discussionsupporting
confidence: 59%
“…The complication rate was comparable in this sample, with five of the eight patients presenting a complication [37]. Spear and Onyewu recently found that, of 40 patients treated from 1990 to 1998 who underwent staged breast reconstruction with an expander and implant and received radiation before, during or after the expansion, 47.5% required an additional flap procedure to improve, correct, or save the implant [46]. The overall complication rate was 52.5%, compared with 10% in a control group of 40 patients who did not undergo irradiation who were randomly sampled from 200 such patients treated during the same period.…”
Section: Discussionmentioning
confidence: 54%
“…7,8 Existing studies of radiation and immediate reconstruction are confounded by small groups of patients with irradiated implants treated with heterogeneous radiotherapy and surgical sequencing and techniques. [9][10][11][12][13][14][15] In addition, the median follow-ups of these studies were relatively short, and end points were variably defined. These differences led to a wide spectrum of reported complication rates ranging from 5% to 48%, underscoring the need for reliable data with lengthy follow-up in homogeneously treated patients who received immediate implantbased reconstruction and radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding, which suggests that both preoperative and postoperative radiotherapy are important predictors of patient satisfaction, is consistent with other published reports. Numerous studies have shown that patients who undergo postmastectomy, implant-based reconstruction after the receipt of preoperative chest wall irradiation have a higher incidence of complications, including capsular contracture, 19,[24][25][26] and that the receipt of postmastectomy adjuvant radiotherapy is correlated with both the development of complications and increased patient dissatisfaction. [27][28][29][30] Thus, the determination of effect size herein allowed clinically meaningful comparisons to be made between the effects of a known entity (such as postmastectomy radiotherapy) versus other clinical variables (such as implant type) that may have an impact on patients' satisfaction with their reconstructed breasts.…”
Section: Discussionmentioning
confidence: 99%